Optimization of the Extraction of the Volatile Fraction from Honey Samples by SPME-GC-MS, Experimental Design, and Multivariate Target Functions - Elisa Robotti; Federica Campo; Marta Riviello; Marco Bobba; Marcello Manfredi; Eleonora Mazzucco; Fabio Gosetti; Giorgio Calabrese; Emanuele Sangiorgi; Emilio Marengo (Journal of Chemistry)
Head space (HS) solid phase microextraction (SPME) followed by gas chromatography with mass spectrometry detection (GC-MS) is the most widespread technique to study the volatile profile of honey samples. In this paper, the experimental SPME conditions were optimized by a multivariate strategy. Both sensitivity and repeatability were optimized by experimental design techniques considering three factors: extraction temperature (from 50°C to 70°C), time of exposition of the fiber (from 20 min to 60 min), and amount of salt added (from 0 to 27.50%). Each experiment was evaluated by Principal Component Analysis (PCA) that allows to take into consideration all the analytes at the same time, preserving the information about their different characteristics. Optimal extraction conditions were identified independently for signal intensity (extraction temperature: 70°C; extraction time: 60 min; salt percentage: 27.50% w/w) and repeatability (extraction temperature: 50°C; extraction time: 60 min; salt percentage: 27.50% w/w) and a final global compromise (extraction temperature: 70°C; extraction time: 60 min; salt percentage: 27.50% w/w) was also reached. Considerations about the choice of the best internal standards were also drawn. The whole optimized procedure was than applied to the analysis of a multiflower honey sample and more than 100 compounds were identified.